Change of Some Soil Quality Characteristics under Different Pasture Reclamation Methods of Rangelands - Cafer Türkmen; Nuray Müftüoğlu; Yasemin Kavdır (Journal of Agricultural Sciences)
The present study was conducted to investigate the effects of different pasture reclamation methods on soil characteristics. For this purpose, soil samples were taken from 0–15 and 15–30 cm depths of the pasture lands subjected to 5 different reclamation processes from 8 different locations of each process during the second week of May of 2008 and 2009. Soil reaction, soil salinity, lime content, total carbon, total nitrogen, aggregate stability, bulk density, particle density, catalase and urease enzyme activities and mesophyllic aerobic microorganism count tests were carried out on soil samples for two years. Effects of reclamation processes on soil reaction, soil salinity, lime content, total nitrogen, aggregate stability, catalase enzyme activity and mesophyllic microorganism counts found to be significant at P<0.01 level. Effects of treatments on total carbon and urease enzyme activity were found to be significant at P<0.05 level. Effects of soil depth on soil salinity, total carbon, catalase and urease enzyme activities were found to be significant at P<0.01 level; soil reaction, total nitrogen, aggregate stability, bulk density, partical density and mesophyllic microorganism counts were found to be significant at P<0.05 level. Interactions of treatments and depth were not significant at any level.